Fatty acid profiling of bovine milk and cheese from six European areas by GC‐FID and GC‐MS. (5th November 2020) - Eisenstecken, Daniela; Stanstrup, Jan; Robatscher, Peter; Huck, Christian W.; Oberhuber, Michael
Abstract : The fatty acid (FA) composition of milk from six European areas, as well as the alteration in the FA profile during cheese production, was studied using both a targeted GC‐FID and an untargeted GC‐MS approach. By applying principal component, partial least square discriminant and chemical similarity enrichment analysis, a discrimination of the geographical areas could be achieved highlighting important FA classes such as odd‐ and branched‐chain FAs for the differentiation. The FA profile remained constant during cheese production, and aroma compounds have been identified as biomarkers for the ripening methods used, namely foil and smear ripening. Abstract : GC‐FID‐ and GC‐MS‐based fatty acid profiling as a tool trace differences of bovine bulk milk and cheese produced thereof.